Ionizing Radiation Induces Morphological Changes and Immunological Modulation of Jurkat Cells - Voos, Patrick; Fuck, Sebastian; Weipert, Fabian; Babel, Laura; Tandl, Dominique; Meckel, Tobias; Hehlgans, Stephanie; Fournier, Claudia; Moroni, Anna; Rödel, Franz; Thiel, Gerhard (Frontiers in Immunology, 2018)
Impairment or stimulation of the immune system by ionizing radiation (IR) impacts on immune surveillance of tumor cells and non-malignant cells and can either foster therapy response or side effects/toxicities of radiation therapy. For a better understanding of the mechanisms by which IR modulates T-cell activation and alters functional properties of these immune cells, we exposed human immortalized Jurkat cells and peripheral blood lymphocytes (PBL) to X-ray doses between 0.1 Gy and 5 Gy. This resulted in cellular responses, which are typically observed also in naïve T-lymphocytes in response of T-cell receptor immune stimulation or mitogens. These responses include oscillations of cytosolic Ca2+, an up-regulation of CD25 surface expression, interleukin-2 and interferon-gamma synthesis, elevated expression of Ca2+ sensitive K+ channels and an increase in cell diameter. The latter was sensitive to inhibition by the immunosuppressant cyclosporine A, Ca2+ buffer BAPTA-AM and the CDK1-Inhibitor RO3306, indicating the involvement of Ca2+-dependent immune activation and radiation induced cell cycle arrest. Further, on a functional level, Jurkat and PBL cell adhesion to endothelial cells was increased upon radiation exposure and was highly dependent on an up-regulation of integrin beta-1 expression and clustering. In conclusion, we here report that ionizing radiation impacts on immune activation and functional properties of T-lymphocytes that may have implications in both toxic effects and treatment response to combined radiation and immune therapy in cancer patients.